iBox: Internet in a Box - Ashok, Sachin; Duvvuri, Sai Surya; Natarajan, Nagarajan; Padmanabhan, Venkat; Sellamanickam, Sundararajan; Gehrke, Johannes (ACM HotNets 2020, 2020)
We present a vision of data-informed network simulation to address significant shortcomings in the state of the art. We substantiate our position with proof points based on iBox, which leverages networking domain knowledge and machine learning (ML) models, coupled with plentiful data, to provide a pathway to perpetual renewal of network simulators.